Three-dimensional Thai dessert printing: A preliminary study on Khanom Ar-Lua - Chansri, Natthavika; Yindee, Wachiraporn; Pattamanawin, Suttinee; Phattanaphibul, Thittikorn (Agriculture and Natural Resources, 2023)
Importance of the work: Thai desserts require a lot of time to form their exquisite shapes. Three-dimensional (3D) printing may improve this process. Objectives: To investigate the possibility of applying 3D printing in the Thai dessert industry. Materials & Methods: A printing substrate was prepared according to the ingredients for cooking “Khanom Ar-Lua”. An extrusion-based, 3D printing technique was applied to create specimens. In addition, a new mechanical extrusion system was constructed and tested for its dimensional controllability of the deposited substrate. Results: The results of the printed substrate showed good raster width, including consistency and repeatability. There were problems with misalignment between printed layers and the long drying time after the shaping step. Main finding: 3D printing technology showed potential for application in the Thai dessert industry to improve the processing time spent in the shaping step. Further study will investigate using a 3D scanner and reverse engineering technology to prepare digital records of the exquisite shapes of Thai desserts that cannot be easily generated using a computer-aided design package.